Brain tryptophan metabolism on the 5-hydroxytryptamine and kynurenine pathways in a strain of rats with a deficiency in platelet 5-HT. - Joseph, M H (1978)
1 Brain 5-hydroxytryptamine (5-HT) metabolism has been compared in albino (Sprague-Dawley; SD) and in Fawn-Hooded (FH) rats, which have an inherited platelet 5-HT deficiency. 2 It was confirmed that blood 5-HT levels in the FH rats were about one quarter of those in the SD rats. 3 Brain 5-HT and 5-HIAA were however higher in FH rats on a per gram basis; there was no difference between the strains on a per brain basis, because of the smaller brain weights of the FH rats. 4 Brain and plasma tryptophan were not significantly different in the two strains. Plasma kynurenine was higher in the FH rats, and brain kynurenine was also higher either on a per gram or on a per brain basis. 5 The reserpine-releasable brain 5-HT was the same proportion of total brain 5-HT in the two strains. 6 Experiments with pargyline suggested that the turnover of 5-HT was somewhat higher in the FH rats on a per gram basis, but not significantly so on a per brain basis. 7 It is concluded that although brain tryptophan metabolism may be somewhat accelerated along both the 5-HT and kynurenine pathways in the FH rats there is no gross deficiency in the binding of 5-HT in their brains analogous to that found in their platelets.